Integrated Weed Management Systems to Control Common Ragweed (Ambrosia artemisiifolia L.) in Soybean - Beam, Shawn C.; Cahoon, Charles W.; Haak, David C.; Holshouser, David L.; Mirsky, Steven B.; Flessner, Michael L. (Frontiers in Agronomy, 2021)
As resistance to herbicides limits growers' weed management options, integrated weed management (IWM) systems that combine non-chemical tactics with herbicides are becoming critical. A 2 year integrated weed management (IWM) study was conducted at three locations in VA, USA. The factorial study evaluated: (1) soybean planting date (early or late planted) (2) with or without winter cover (cereal rye/wheat or no cover), and (3) with or without harvest weed seed control (HWSC). Prior to soybean planting in the first year, winter cover resulted in a 22% reduction in common ragweed density compared to no cover. At soybean harvest in the first year, the lowest common ragweed densities were in the late planted plots following winter wheat, and common ragweed aboveground biomass was reduced by 46 and 22% at two locations in late planted compared to early planted soybean. To evaluate the impact of the first year's treatments and HWSC, full season soybeans were planted across the trial in the second year. Prior to soybean planting in the second year, late planting in the first year common ragweed density was reduced by 83% at one location, but significant reductions were not observed elsewhere. When comparing winter cover to no cover, common ragweed densities were reduced by 31 and 49% at two locations and densities were similar at the third location. Harvest weed seed control reduced common ragweed density by 43% at one location compared to the conventional harvest plots but no significant reductions were observed at the other locations or at other rating timings. However, there was a significant location by planting date by winter cover interaction and the overall lowest common ragweed densities (4.1 to 10.3 plants m−2) were in the late planted plots with winter cover. This research indicated that winter cover, late planting, and HWSC can reduce common ragweed populations with late planting being the most influential. Therefore, double-cropping soybean after wheat is likely the most viable means to better control common ragweed using IWM as it combines both winter cover and late planting date.